2004
DOI: 10.1111/j.1365-2222.2004.01874.x
|View full text |Cite
|
Sign up to set email alerts
|

A dose‐ranging study of the effects of mequitazine on actual driving, memory and psychomotor performance as compared to dexchlorpheniramine, cetirizine and placebo

Abstract: It was concluded that mequitazine is mildly sedating. The effects of mequitazine are comparable to those of other second-generation antihistamines, in that it causes mild driving impairment, particularly at higher doses.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
63
2

Year Published

2004
2004
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 57 publications
(67 citation statements)
references
References 37 publications
(52 reference statements)
2
63
2
Order By: Relevance
“…Dexchlorpheniramine (6 mg) significantly impaired driving performance after immediate administration in 18 healthy volunteers. 17 A second study in 15 other healthy volunteers confirmed these findings 17 : again, driving performance was significantly impaired after onetime administration of dexchlorpheniramine, 6 mg (⌬SDLP of approximately 2 cm). After 8 days of treatment, SDLP did not differ significantly from placebo.…”
Section: First-generation Antihistaminessupporting
confidence: 66%
See 2 more Smart Citations
“…Dexchlorpheniramine (6 mg) significantly impaired driving performance after immediate administration in 18 healthy volunteers. 17 A second study in 15 other healthy volunteers confirmed these findings 17 : again, driving performance was significantly impaired after onetime administration of dexchlorpheniramine, 6 mg (⌬SDLP of approximately 2 cm). After 8 days of treatment, SDLP did not differ significantly from placebo.…”
Section: First-generation Antihistaminessupporting
confidence: 66%
“…However, ⌬SDLP was less that that observed with a BAC of 0.05% and not significant on day 4. Recent studies 17,30 in healthy volunteers confirmed that cetirizine (10 mg) does not significantly impair driving performance.…”
Section: Second-generation Antihistaminesmentioning
confidence: 94%
See 1 more Smart Citation
“…[18][19] On the other hand, there are also studies that did not find behavioral effects of Cetirizine. [20][21] The 2nd-generation antihistamines represent a major triumph for the pharmaceutical industry in reducing potential side effects; there still remains some evidence that all antihistamines, even the 2nd-generation drugs, can have objective skills impairment consequences at least in some cases. [22] The present study included 50 healthy volunteers where males and females had equal representation.…”
Section: Discussionmentioning
confidence: 99%
“…11) Recent studies have demonstrated its potential use for the treatment of allergic conjunctivitis, and for its possible sedative properties. 12) As a consequence the development of efficient synthesis of 1 is of prime importance for clinical evaluations, and more importantly for the elucidation of the mechanism of action with different biological targets and receptors. The existing strategies for the preparation of mequitazine 1, most of which have been patented, rely mainly on the construction of the C9-N bond, either by alkylation or acylation of phenothiazine using appropriate 3-substituted quinuclidine electrophiles.…”
mentioning
confidence: 99%